The Implementation TPACK in Elementary School - Annida Lathifa Riandy Putri; Winarno; Tri Murwaningsih (International Journal of Elementary Education, 2023)
Industrial Revolution 4.0 requires teachers to master technology to be integrated into learning. This research aims to analyze the application of Technology, Pedagogy, and Content Knowledge (TPACK) in the post-online learning process. This research is classified as descriptive qualitative research using mixed methods with a sequential exploratory strategy. The subjects involved in this research were 20 class teachers. The data collection used in this research is data collection through interviews, observation, and documentation. The instrument used to collect data for this research is a questionnaire. The data obtained from this research will be analyzed using inductive model analysis techniques. The research results show that in implementing TPACK, many teachers, especially older ones, still need help operating technology well. Apart from that, teachers have yet to be able to utilize technology to create new representations. The teacher only provides learning content based on students' books and several examples from Google and YouTube. Therefore, teachers need to understand aspects of TPACK. This research implies that all stakeholders will be able to realize the importance of ICT because using learning media using technology aims to develop a curriculum in schools to improve the quality of education.